Characterization of atypical language activation patterns in focal epilepsy. Issue 1 (2nd January 2014) - Berl, Madison M.; Zimmaro, Lauren A.; Khan, Omar I.; Dustin, Irene; Ritzl, Eva; Duke, Elizabeth S.; Sepeta, Leigh N.; Sato, Susumu; Theodore, William H.; Gaillard, William D.
<x xml:space="preserve">Abstract</x> Objective Functional magnetic resonance imaging is sensitive to the variation in language network patterns. Large populations are needed to rigorously assess atypical patterns, which, even in neurological populations, are a minority. Methods We studied 220 patients with focal epilepsy and 118 healthy volunteers who performed an auditory description decision task. We compared a data‐driven hierarchical clustering approach to the commonly used a priori laterality index (LI) threshold (LI < 0.20 as atypical) to classify language patterns within frontal and temporal regions of interest. We explored (n = 128) whether IQ varied with different language activation patterns. Results The rate of atypical language among healthy volunteers (2.5%) and patients (24.5%) agreed with previous studies; however, we found 6 patterns of atypical language: a symmetrically bilateral, 2 unilaterally crossed, and 3 right dominant patterns. There was high agreement between classification methods, yet the cluster analysis revealed novel correlations with clinical features. Beyond the established association of left‐handedness, early seizure onset, and vascular pathology with atypical language, cluster analysis identified an association of handedness with frontal lateralization, early seizure onset with temporal lateralization, and left hemisphere focus with a unilateral right pattern. Intelligence quotient was not significantly different among patterns. Interpretation Language dominance is a continuum; however, our results demonstrate meaningful thresholds in classifying laterality. Atypical language patterns are less frequent but more variable than typical language patterns, posing challenges for accurate presurgical planning. Language dominance should be assessed on a regional rather than hemispheric basis, and clinical characteristics should inform evaluation of atypical language dominance. Reorganization of language is not uniformly detrimental to language functioning. ANN NEUROL 2014;75:33–42